The Effect of Taxpayer Awareness, Socialization, Sanctions and Accountability on Motor Vehicle Taxpayer Compliance - Habibah, Marsa; Kusuma, Indra Cahya; Aziz, Ayi Jamaludin (Institut Bisnis dan Informatika Kesatuan, 2024)
This study examines the influence of awareness, tax socialization, tax sanctions, and public service accountability on motor vehicle taxpayer compliance in Bogor City. Using a quantitative descriptive approach, this study involved 400 respondents selected using the simple random sampling method. Data were collected through structured interviews, observations, and questionnaires, and tested for validity and reliability. The data fulfillment test ensured that the regression was met, including normality, multicollinearity, and heteroscedasticity. The results of the study indicate that awareness and public service accountability have a significant effect on taxpayer compliance, emphasizing the importance of providing clear information and quality services. Tax sanctions also have a positive effect, indicating that the provision of appropriate sanctions can encourage people to comply with paying taxes. However, tax socialization did not have a significant impact on compliance, indicating that the dissemination of information alone is not effective enough. This study highlights the important role of the government in improving tax compliance through strategies that include public awareness, strict application of sanctions, and public service accountability. These findings provide insight for policy makers to design a more effective tax system that can increase state revenue.